2014
DOI: 10.1007/s00520-014-2181-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dance on cancer-related fatigue and quality of life

Abstract: Dance might be an appropriate, effective approach for treatment of cancer-related fatigue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 28 publications
2
28
1
1
Order By: Relevance
“…Due to these limitations, only a trend towards the improvement of well-being for patients and their healthy partners may be derived. This trend is in line with the benefits that have been described in other dance movement therapy programs (14,15,19).…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…Due to these limitations, only a trend towards the improvement of well-being for patients and their healthy partners may be derived. This trend is in line with the benefits that have been described in other dance movement therapy programs (14,15,19).…”
Section: Discussionsupporting
confidence: 73%
“…As the recruitment of patients to a study on dance movement therapy with elaborate assessment tools is difficult (19), it was decided to attempt a stepwise development of the questionnaire, in accordance with the wishes of the participants. After the first session in April, the participants spontaneously remarked that they were highly pleased that an assessment was not required, as they had expected from a course free of charge.…”
Section: Study Evaluationmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall scientific evidence suggests that exercise is safe and feasible to be applied as non-pharmacological intervention for the treatment of cancer and it can also improve aspects such as quality of life and psychophysiological function 12,13 . Consistent results include how exercise effects the reduction in fatigue condition 14 , postural changes, on muscular fibrosis and/or tissue adhesion of surgical area 15 , in depression, anxiety and anguish, combined with positive changes in parameters of physical fitness, aerobic capacity and general muscle function 13,16 . The dance application is pointed out in several studies as one of the possibilities of adjuvant therapies, as in cancer patients 14 hemophilia patients 17 , elderly with depression 18 and people with Parkinson disease 19 .…”
Section: Introductionmentioning
confidence: 93%
“…The study revealed that the intervention group participating in the dance program presented significant improvement in cancer-associated fatigue, as well as in emotional and social functioning, and in physical performance (Sturm et al, 2014). The study conducted by Koch et al (2014) upon the effectiveness of dance movement and dance in general as a therapeutic tool for the treatment of psychological problems related to health and QoL has shown that dance is effective in improving QoL and reducing clinical symptoms, such as depression and anxiety.…”
Section: Health-related Quality Of Life (Hrqol) and Dancementioning
confidence: 99%